2015
DOI: 10.1371/journal.pone.0141341
|View full text |Cite
|
Sign up to set email alerts
|

Everything in Moderation - Dietary Diversity and Quality, Central Obesity and Risk of Diabetes

Abstract: Diet guidelines recommend increasing dietary diversity. Yet, metrics for dietary diversity have neither been well-defined nor evaluated for impact on metabolic health. Also, whether diversity has effects independent of diet quality is unknown. We characterized and evaluated associations of diet diversity and quality with abdominal obesity and type II diabetes (T2D) in the Multi-Ethnic Study of Atherosclerosis. At baseline (2000–02), diet was assessed among 5,160 Whites, Hispanic, Blacks, and Chinese age 45–84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(124 citation statements)
references
References 30 publications
8
104
5
2
Order By: Relevance
“…1 Esto se refleja en una disminución del gasto per cápita en alimentos recomendables como frutas, verduras, lácteos y carnes, y en un mayor gasto en alimentos densos en energía (como cereales refinados y comida rápida) y bebidas azucaradas. 2 Existe evidencia sobre la asociación del consumo de grupos de alimentos como cereales refinados, dulces, bebidas azucaradas y alimentos procesados de origen animal con la ganancia de peso y enfermedades crónicas; [3][4][5] por ello, se recomienda no consumirlos de forma cotidiana. En México, se ha reportado que los patrones de alimentación basados en este tipo de alimentos se asocian positivamente con el riesgo de presentar sobrepeso u obesidad en escolares y adultos.…”
unclassified
“…1 Esto se refleja en una disminución del gasto per cápita en alimentos recomendables como frutas, verduras, lácteos y carnes, y en un mayor gasto en alimentos densos en energía (como cereales refinados y comida rápida) y bebidas azucaradas. 2 Existe evidencia sobre la asociación del consumo de grupos de alimentos como cereales refinados, dulces, bebidas azucaradas y alimentos procesados de origen animal con la ganancia de peso y enfermedades crónicas; [3][4][5] por ello, se recomienda no consumirlos de forma cotidiana. En México, se ha reportado que los patrones de alimentación basados en este tipo de alimentos se asocian positivamente con el riesgo de presentar sobrepeso u obesidad en escolares y adultos.…”
unclassified
“…The Family Affluence Scale (FAS) index was used as an indicator of the adolescents' material affluence (reflecting family expenditure and consumption) [19]. The scale ranged from 0 to 8 and was re-coded and dichotomized into a 2-point scale: Blow familial wealth^(0-4) and Bhigh familial wealth^ (5)(6)(7)(8). Maternal educational level was also recorded (primary education, lower secondary education, higher secondary education, or university degree) and recorded later into a 2-point scale, namely as a low (primary and lower secondary education) and high (higher secondary education and university degree score) education.…”
Section: Sociodemographic Factors (Socioeconomic Status and Educationmentioning
confidence: 99%
“…While the MDS is characterized by a high intake of vegetables, legumes, fruits, nuts, and cereal grains, moderate-to-high fish intakes, and high intakes of unsaturated lipids but low intakes of saturated fats, together with low intake of meat products, the DQI is more based upon principles of balance and variation, including considering that all foods and food groups (including dairy and meat products) may contribute to a healthy diet. These indices are indicators of the overall diet and are known to be inversely associated with mortality in adults [5], as well as with a number of chronic diseases including cardiovascular diseases [6,7], obesity, and type 2 diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a healthy lifestyle and nutrition help the physical, intellectual, and social health of the individual, improve the quality of life, and reduce the cost of socio-healthy cares (8). According to the WHO, more than 80% of obesity-related illnesses can be treated by improving the quality of life and physical activity (9).…”
Section: Introductionmentioning
confidence: 99%